Further undescribed cembranoids from South China Sea soft coral Sarcophyton ehrenbergi: Structural elucidation and biological evaluation. (February 2023) - Wu, Meng-Jun; Yu, Dan-Dan; Du, Ye-Qing; Zhang, Juan; Su, Ming-Zhi; Jiang, Cheng-Shi; Guo, Yue-Wei
Abstract: A detailed chemical investigation of the South China Sea soft coral Sarcophyton ehrenbergi has yield seven undescribed cembranoids, namely isoehrenbergol D and sarcoehrenolides F–K embodying a rare α, β -unsaturated-lactone moiety at C-6 to C-19, along with two known related compounds, ehrenbergol D and sarcoehrenolide A. Their structures and absolute configurations were unambiguously established in the light of extensive spectroscopic data analysis, modified Mosher's method, X-ray diffraction analysis, and quantum chemical computation method. In a bioassay for α -glucosidase inhibition, ehrenbergol D was evaluated as α -glucosidase inhibitor with an IC50 value of 13.57 μM. Graphical abstract: Seven undescribed cembranoids and two known analogs were isolated and identified from the soft coral Sarcophyton ehrenbergi . The α -glucosidase inhibitory activity of these compounds was evaluated. Image 1 Highlights: Seven undescribed cembranoids were isolated from the soft coral Sarcophyton ehrenbergi. Those cembranoids featured a rare α, β -unsaturated-lactone moiety at C-6 to C-19. Ehrenbergol D was evaluated as α -glucosidase inhibitor with an IC50 value of 13.57 μM.